Aeroplane at San Luis Obispo, Cal., July 4, 1910. - Frank Aston::::::photographer::: (1910)
Aeroplane at San Luis Obispo, Cal., July 4, 1910. This is believed to be the first flight above San Luis Obispo. Photograph taken from Terrace Hill, looking north.